1937
DOI: 10.1172/jci100840
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Circulatory Collapse Induced by Sodium Nitrite 1

Abstract: The study to be reported was undertaken with the purpose of thr.owing light on the mechanism of vasomotor collapse in man. During a previous investigation (1), it was noted that small doses of sodium nitrite, which in normal subjects would produce no symptoms and slight if any circulatory changes in the prone position, would in the upright position lead to progressive vasomotor collapse, often terminating in syncope. Return to the prone position was followed by immediate recovery without ill effects. By varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1937
1937
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(33 citation statements)
references
References 11 publications
(13 reference statements)
1
32
0
Order By: Relevance
“…56 59 ; and Ignarro and Gruetter 60 ). However, the high micromolar to millimolar concentrations of nitrite necessary to achieve these effects contrasted with the low nanomolar concentrations of authentic NO needed to vasodilate aortic rings.…”
Section: Physiologic Effects Of Nitrite Reactions With Hemoglobinmentioning
confidence: 99%
“…56 59 ; and Ignarro and Gruetter 60 ). However, the high micromolar to millimolar concentrations of nitrite necessary to achieve these effects contrasted with the low nanomolar concentrations of authentic NO needed to vasodilate aortic rings.…”
Section: Physiologic Effects Of Nitrite Reactions With Hemoglobinmentioning
confidence: 99%
“…Some studies have suggested that the vasodilatation seen in neurally mediated syncope results from a withdrawal of sympathetic tone (14)(15)(16). Consistent with this view, there is evidence of reduced cardiac and renal norepinephrine (NorEpi) 1 spillover in patients who fainted during cardiac catheterization (17).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study of the vasomotor collapse induced by sodium nitrite in normal subjects in the upright position has revealed that the state of collapse is accompanied by a fall in venous pressure and an inadequate return of venous blood to the heart from the lower half of the body (1).…”
mentioning
confidence: 99%